2023
DOI: 10.1101/2023.01.20.524877
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Task-specific patterns of odorant receptor expression in worker antennae indicates a sensory filter regulating division of labor in ants

Abstract: Division of labor (DOL) is a characteristic trait of insect societies, where tasks are generally performed by groups of specialized individuals. In social insects, young workers perform duties within the safety of the nest (e.g., brood care), while older ones undertake riskier tasks (e.g., foraging for food). This DOL remains dynamic, and workers may switch back and forth when colony needs require. Theoretical models propose that workers differ in their thresholds to take on certain tasks when confronted to ta… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 150 publications
2
11
0
Order By: Relevance
“…One candidate we identified among the genes differing between the ants transferred into the original treatment or a colony containing unrelated individuals and/or social parasites was a homologue to the odorant receptor 49b‐like in Temnothorax curvispinosus and most similar to lace_OR205 from the manual annotations of ORs from our focal species (Appendix S1; Jongepier et al, 2022). We additionally used blastn to find the most similar sequence among the ORs previously identified in a closely related species, Temnothorax longispinosus (Jongepier et al, 2022), which has been identified to be from subfamily I3 (Caminer et al, 2023). This subfamily is predicted to have an especially important role since it only occurs once in the genome of many species including L. acervorum according to our BLAST results (Engsontia et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One candidate we identified among the genes differing between the ants transferred into the original treatment or a colony containing unrelated individuals and/or social parasites was a homologue to the odorant receptor 49b‐like in Temnothorax curvispinosus and most similar to lace_OR205 from the manual annotations of ORs from our focal species (Appendix S1; Jongepier et al, 2022). We additionally used blastn to find the most similar sequence among the ORs previously identified in a closely related species, Temnothorax longispinosus (Jongepier et al, 2022), which has been identified to be from subfamily I3 (Caminer et al, 2023). This subfamily is predicted to have an especially important role since it only occurs once in the genome of many species including L. acervorum according to our BLAST results (Engsontia et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Other differences between parasitic and non‐parasitic nests, such as a general increase in aggression in parasitic nests, may nevertheless be transcriptionally detectable, for example, in the expression of stress‐related genes. Therefore, we specifically investigated genes related to sensory perception, in particular, odorant receptors, whose expression changes in response to the social environment of ant larvae (Pulliainen et al, 2021) and varies between workers mainly performing tasks inside or outside the nest (Caminer et al, 2023). Odorant receptors, particularly those of the 9‐exon gene family, are known to bind to cuticular hydrocarbons, which play an important role in communication in social insects (Pask et al, 2017; Slone et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, workers of the ant Temnothorax longispinosus that highly express Vitellogenin-like A ( Vg-like A ) have an increased responsiveness to brood stimuli and display high brood care activity [8,9]. In line with this, half of all 419 odorant receptors are differentially expressed in the antennae of brood carers and foragers in this species, pointing to vastly different sensitivity to chemical cues [10]. Workers can transition multiple times between different behavioural states.…”
Section: Introductionmentioning
confidence: 99%
“…To address this, we used acorn ant T. longispinosus in which workers specialize in brood care or foraging, and task specialization is linked to age, fertility and distinct transcriptional profiles [8][9][10]24,32]. We manipulated colony demography to induce task switching and coupled these manipulations with the application of inhibitors of p300/CBP histone acetyltransferase (HAT) to disentangle the effects of demand and HAT activity on task specialization.…”
Section: Introductionmentioning
confidence: 99%